Broadening the Lens on the Science of Reading: A Multifaceted Perspective on the Role of Academic Language in Text Understanding. (16th September 2020) - Phillips Galloway, Emily; McClain, Janna Brown; Uccelli, Paola
ABSTRACT: Merging evidence from psychological models of reading comprehension, ethnographic research on language and literacy, and textual linguistics lines of research, the authors take the position that psychological models of reading comprehension often overlook written language comprehension and production as context‐embedded, sociocultural processes. Using the example of academic language comprehension by middle grade learners, the authors present a series of studies that have informed the science of reading by making visible a precise set of high‐utility academic language skills that support informational text comprehension during middle childhood (ages 9–14). Studies have suggested that these skills develop gradually throughout adolescence and significantly contribute to reading comprehension. Drawing on this research with the goal of informing the science of reading, the authors suggest that academic language comprehension involves for the reader (a) familiarity with a set of academic language forms commonly found in school texts, (b) experience with the sociocultural practices of understanding and using the academic language of text within a particular sociocultural community, and (c) aligning with or resisting the reader identities implied by the language of a text. The authors suggest that innovative research and pedagogical approaches are needed to broaden the conceptualization of language and reading comprehension relations from purely cognitive into one that embraces the reader's interaction with a text as a sociocultural phenomenon.